Preparation method of 3D-printable macroporous frozen gel integral adsorbent and application of 3D-printable macroporous frozen gel integral adsorbent in selective palladium separation
By developing large-pore frozen gels containing amidoxime sites and combining 3D printing technology, the limitations and mechanical stability of palladium adsorbent materials in industrial scale implementation are solved, and efficient and economical palladium ion recovery is achieved, satisfying the satisfaction of The demand for industrial applications.
Patent Information
- Application Number
- CN202411334877.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-24
AI Technical Summary
The existing palladium adsorbent materials have limitations in the industrial scale implementation, and the mechanical stability challenges of frozen gels in large-scale preparation are great, making it difficult to achieve efficient and economical palladium recycling.
By developing macroporous frozen gels containing amidoxime sites and combining 3D printing technology, adsorbents with high mechanical strength and customized shapes are prepared to achieve selective separation and efficient recovery of palladium ions.
It significantly improves the adsorption capacity and selectivity of palladium ions, enhances the mechanical strength and operating flexibility of the material, realizes cost-effective palladium recycling, conforms to the concept of green chemistry, and shows excellent recycling efficiency in practical applications.
Smart Images

Figure CN119176973A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adsorption and separation functional materials, and relates to the preparation of a macroporous cryogel monolithic adsorbent for selective adsorption and separation of palladium, and in particular to the preparation and 3D printing customization of a macroporous cryogel containing amidoxime sites, and its application in the selective adsorption and separation of palladium ions. Background Art
[0002] Palladium is a precious metal with excellent physical and chemical properties, which is widely used in jewelry manufacturing, multilayer ceramic capacitors, biomedicine, high catalysis, electrical technology, energy storage and other fields. However, due to the limited reserves of palladium in the earth's crust, the contradiction between supply and demand is becoming increasingly prominent. According to data from the London International Financial Futures and Options Exchange (LIFFE), the highest trading price of palladium in 2021 reached US$3,010 per ounce, significantly higher than platinum ($1,337 per ounce) and gold ($1,959 per ounce). Its high price reflects the scarcity of palladium in the market and its importance. Therefore, it is particularly important to find alternative sources of palladium and to recover palladium from secondary resources.
[0003] Although palladium is present in low concentrations in ores, typically between 2 and 6 g / ton, the process of extracting palladium from ores is time-consuming, labor-intensive and costly. In contrast, the palladium content in discarded circuit boards, automotive catalytic converters and industrial catalysts is relatively high, typically between 100 and 10,000 g / ton, and the process of recovering palladium from these secondary resources is relatively simple and inexpensive. In recent years, researchers have developed a variety of techniques for extracting palladium from secondary resources, including adsorption, solvent extraction, precipitation and biorecovery. Among them, adsorption has attracted much attention due to its advantages such as low cost, high efficiency and simple operation. Many adsorbent materials have been developed for the adsorption of palladium, which show excellent adsorption efficiency and selectivity under acidic conditions. However, their powdery nature has certain limitations in industrial-scale implementation.
[0004] To overcome the above limitations, researchers have begun to focus on the development of macroporous materials, which have sponge-like properties and three-dimensional interconnected structures suitable for industrial-scale implementation. The adsorption capacity of adsorbent materials for various targets can be significantly improved by introducing functional groups such as amide, amine, sulfonic acid, and oxime groups into the polymer network. Among them, oxime groups perform well in capturing precious metals and heavy metals, but in addition to functional groups, the porosity of the material also plays a vital role in accelerating the adsorption process. Therefore, the development of new material strategies with macroporous morphology, enhanced functionality, high cost-effectiveness, and large adsorption capacity is of great significance in contemporary industry.
[0005] Cryopolymerization is a synthetic route for the efficient development of macroporous materials under cryogenic conditions. The cryopolymerization method promotes the formation of three-dimensional macroporous structures through the freeze-concentration effect at sub-zero temperatures, which is superior to the traditional gelation route. Cryogels prepared by this method show broad application prospects in many fields such as energy production, heavy metal removal, dye adsorption, oil-water separation and medical applications. However, it is still quite challenging to achieve mechanical stability in large-scale preparations of samples prepared solely by cryopolymerization.
[0006] In recent years, 3D printing technology has emerged as a revolutionary tool for manufacturing advanced materials, providing unparalleled control over their structure and mechanical properties. By utilizing 3D printing technology, the shape and mechanical strength of cryogels can be precisely customized, enhancing their applicability in various industrial processes. The combination of 3D printing technology and cryopolymerization allows for the precise construction of cryogels with customized shapes. This synergy not only improves the mechanical strength of cryogels, but also enables on-demand shaping, making them suitable for specific palladium recovery applications.
[0007] In summary, this study focused on the development of a macroporous cryogel containing amidoxime sites for efficient and selective recovery of palladium (II) from acidic solutions in secondary resources. The customization of the material shape through 3D printing technology greatly improved the mechanical strength and industrial applicability of the cryogel, providing a new method with great potential for the recovery of precious metals from waste resources, which has not been reported so far. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention proposes an innovative solution, namely, through the preparation of amidoxime functionalized macroporous cryogel (AN-AMPS-AAO) and its customized 3D printing technology, to achieve efficient recovery of palladium ions from secondary resources. This method not only overcomes the limitations of traditional adsorption materials in adsorption capacity, selectivity and recovery mode, but also provides an economical, efficient, environmentally friendly, and large-scale application of palladium recovery technology.
[0009] In order to achieve the above technical purpose, the technical solution adopted by the present invention is as follows:
[0010] Step 1: Preparation of macroporous flexible cryogel (AN-AMPS):
[0011] A certain amount of acrylonitrile (AN), 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and methylenebisacrylamide (MBA) were added into a certain amount of deionized water and stirred continuously until they were completely dissolved; then, the pH value of the solution was adjusted to neutral, which was recorded as solution A;
[0012] Use pure water to prepare the molar concentration of c 1A mixed aqueous solution of tetramethylethylenediamine (TEMED) and ammonium persulfate (APS) is referred to as solution B;
[0013] Place solution A and solution B in a standard refrigerator at -18℃ for a certain period of time. 1 Then, solution A and solution B were mixed in a volume ratio of 1:1 and reacted in a refrigerator at -18°C for a certain time t 2 After the reaction was completed, the sample was thawed at room temperature to melt the ice crystals within the frozen gel 3D network, and then thoroughly washed with a mixed solution of pure water and methanol, and the resulting material was freeze-dried to obtain gel AN-AMPS.
[0014] In step 1, in solution A, the usage ratio of AN, AMPS, MBA and water is 0.75-3 mL: 0.45-1.8 g: 0.12-0.48 g: 12-48 mL;
[0015] In solution B, the molar concentrations of TEMED and APS are c 1 0.03-0.12M;
[0016] Freezing time t 1 The reaction time is 2.5-10min. 2 6-24h.
[0017] Step 2: Preparation of amidoxime functionalized macroporous cryogel (AN-AMPS-AAO):
[0018] Add a certain amount of hydroxylamine hydrochloride (NH 2 OH·HCl), sodium carbonate (Na 2 CO 3 ) and sodium hydroxide (NaOH), the mixed solution is heated to a certain temperature T 1 Then, the gel AN-AMPS obtained in step 1 was added to the mixed solution, and the mixture was stirred at a certain temperature T 2 The reaction time t 3 The resulting cryogel was then freeze-dried to obtain the product AN-AMPS-AAO.
[0019] In step 2, the DMF, NH 2 OH·HCl, Na 2 CO 3 The dosage ratio of NaOH is 50-200mL: 2-8g: 0.75-3g: 0.4-1.6g, and the reaction temperature is T 1 The reaction temperature is 30-40°C. 2 is 60-70℃, reaction time t3 For 10-30h.
[0020] Step 3: Preparation of customized cryogel (3D-AN-AMPS-AAO) using 3D printing technology:
[0021] Sodium alginate, AN-AMPS-AAO and deionized water in a certain mass ratio are uniformly mixed, shaped as required, and then the obtained sample with a customized shape is placed in a certain weight percentage c 2 Calcium chloride (CaCl 2 ) in aqueous solution and allowed to stand for a certain period of time t 4 to ensure thorough cross-linking and curing. Then, the sample was washed with deionized water and freeze-dried to obtain the final 3D cryogel (3D-AN-AMPS-AAO).
[0022] In step 3, the dosage ratio of sodium alginate, AN-AMPS-AAO and deionized water is 50-200 mg: 100-300 mg: 1-4 mL, and calcium chloride (CaCl 2 ) Weight percentage of aqueous solution c 2 4-16wt%, crosslinking and curing time t 4 6-24h.
[0023] The present invention achieves selective separation and efficient recovery of palladium ions by developing a macroporous cryogel containing amidoxime sites and combining it with customized 3D printing technology.
[0024] The beneficial effects of the present invention are:
[0025] (1) High adsorption capacity and selectivity: By introducing amidoxime sites, the adsorption capacity of cryogel for palladium ions is significantly improved. The amidoxime group forms a stable complex with the palladium ions, thereby enhancing the selectivity of the adsorbent for palladium ions. Experiments show that the maximum adsorption capacity of cryogel for palladium ions after oxime treatment reaches 425.32 mg / g, which is much higher than traditional adsorbent materials. Under acidic conditions, amidoxime sites effectively capture palladium ions through electrostatic attraction and complexation. Even in complex systems with multiple coexisting metal ions (such as Ca, Cu, Fe, K, Mg, Ni and Zn), cryogel still shows excellent selectivity.
[0026] (2) Mechanical strength and customized shape: The mechanical strength of the cryogel is significantly enhanced by customizing the cryogel through 3D printing technology. The optimized 3D printing "ink" formula enables it to maintain structural integrity during the 3D printing process, forming a macroporous overall structure with high mechanical strength and stability. 3D printing technology can precisely control the shape of the cryogel to meet the needs of different industrial applications. This customized cryogel has significant advantages in industrial applications. For example, in the palladium recovery process, it can be printed into a specific shape according to actual needs, which improves the flexibility and efficiency of the operation.
[0027] (3) Environmentally friendly and economically efficient: The cryopolymerization reaction is carried out at sub-zero temperatures, which significantly reduces energy consumption and conforms to the concept of green chemistry. Compared with traditional high-temperature synthesis methods, the cryopolymerization reaction not only has low energy consumption, but also has a more ideal pore structure of the product. In the preparation process of cryogel, no large amount of organic solvents are required, which reduces environmental pollution.
[0028] (4) Effectiveness in practical applications: Through actual testing of waste catalyst samples, the cryogel's ability to efficiently recover palladium ions in real industrial waste liquids was verified. The experimental results show that cryogel exhibits excellent selectivity and adsorption efficiency in complex waste liquid systems and has high practical application value. Cryogel can effectively recover palladium from secondary resources such as discarded electronic products and automotive catalytic converters, which is in line with the country's strategic requirements for efficient resource recycling and green and low-carbon economic development.
[0029] In summary, the present invention achieves efficient and selective recovery of palladium ions by developing amidoxime-functionalized macroporous cryogels and combining them with customized 3D printing technology, which has significant economic and environmental benefits. This technology not only demonstrates excellent performance on a laboratory scale, but also has the potential for promotion and application on an industrial scale, providing an innovative solution for the efficient recovery of precious metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Figures ad are scanning electron microscope images of AN-AMPS-AAO prepared in Example 1 at different resolutions.
[0031] Figure 2 This is the mercury injection test data of AN-AMPS-AAO prepared in Example 1.
[0032] Figure 3 The infrared spectra of the cryogels at various stages prepared in Example 1.
[0033] Figure 4 This is a photo of the 3D printed customized 3D-AN-AMPS-AAO cryogel adsorbent prepared in Example 1.
[0034] Figure 5 The effect of pH value on the adsorption capacity of palladium ions by the AN-AMPS-AAO cryogel adsorbent prepared in Example 1.
[0035] Figure 6 The adsorption kinetics of palladium ions by the AN-AMPS-AAO cryogel adsorbent prepared in Example 1 and its model fitting curve data.
[0036] Figure 7 The effect of temperature on the adsorption equilibrium of palladium ions by the AN-AMPS-AAO cryogel adsorbent prepared in Example 1 and its model fitting curve data graph.
[0037] Figure 8 This is the adsorption selectivity data diagram of the AN-AMPS-AAO cryogel adsorbent prepared in Example 1.
[0038] Fig. 9 This is a graph showing the adsorption regeneration performance data of the AN-AMPS-AAO cryogel adsorbent prepared in Example 1. DETAILED DESCRIPTION
[0039] In a specific embodiment of the present invention, the recognition performance evaluation is carried out according to the following method: a static adsorption experiment is used to complete the test. 2.0 mg of AN-AMPS-AAO is used to test the adsorption capacity of palladium ions in the pH range of 1.0-4.0. After adsorption, the palladium ion content is determined using an inductively coupled plasma emission spectrometer, and the optimal adsorption pH is determined; then the effect of adsorption time on the adsorption capacity of AN-AMPS-AAO is studied, and the data are fitted and analyzed using a pseudo-first-order model and a pseudo-second-order model; in order to explore the maximum adsorption capacity of AN-AMPS-AAO, we conducted an adsorption equilibrium test in the range of 100-500 ppm of palladium ion concentration, and the Langmuir model and the Freundlich model were used to fit the adsorption data, and the adsorption capacity was calculated based on the results; several other common metal ions in the waste catalyst leachate were selected as competitive adsorbates to study the selective adsorption performance of AN-AMPS-AAO; finally, its adsorption regeneration performance was tested.
[0040] The present invention will be further described below in conjunction with specific implementation examples.
[0041] Embodiment 1:
[0042] (1) Preparation of macroporous flexible cryogel (AN-AMPS)
[0043] 1.5 mL LAN, 0.9 g AMPS and 0.24 g MBA were added to 24 mL deionized water and stirred continuously until completely dissolved. Subsequently, the pH value of the solution was adjusted to neutral and recorded as solution A. A mixed aqueous solution of tetramethylethylenediamine (TEMED) and ammonium persulfate (APS) with a molar concentration of 0.06 M was prepared with pure water and recorded as solution B. Solution A and solution B were placed in a standard refrigerator freezer at -18°C and frozen for 5 minutes, and then solution A and solution B were mixed in a volume ratio of 1:1 and reacted in a refrigerator freezer at -18°C for another 12 hours. After the reaction was completed, the sample was thawed at room temperature to melt the ice crystals in the frozen gel 3D network. Subsequently, it was thoroughly washed with a mixed solution of pure water and methanol, and the resulting material was freeze-dried to obtain AN-AMPS.
[0044] (2) Preparation of amidoxime functionalized macroporous cryogel (AN-AMPS-AAO)
[0045] Add 4 g NH 2 OH·HCl, 1.5 g Na 2 CO 3 and 0.8 g NaOH. The solution was stirred at 35 °C for 3 h. Subsequently, a certain amount of dried cryogel was added to the solution and continued to react at 65 °C for 20 h, and then thoroughly washed with a mixed solution of pure water and methanol. Subsequently, the obtained cryogel was freeze-dried to obtain the product AN-AMPS-AAO.
[0046] (3) Preparation of customized cryogel (3D-AN-AMPS-AAO) using 3D printing technology
[0047] 100 mg sodium alginate, 200 mg AN-AMPS-AAO and 2 mL deionized water were uniformly mixed and shaped as needed, and then the resulting sample with a customized shape was placed in 8 wt % CaCl 2 The sample was then washed with deionized water and freeze-dried to obtain the final 3D cryogel (3D-AN-AMPS-AAO).
[0048] Figure 1 Shown are SEM images of AN-AMPS-AAO at different magnifications. It can be found that the obtained product has a macroporous flake structure with clearly visible surface pores, which is beneficial to mass transfer during the adsorption process.
[0049] Figure 2The mercury intrusion data of AN-AMPS-AAO is shown. It can be seen that the pore size of AN-AMPS-AAO material is mainly concentrated at about 50μm, showing an obvious peak, indicating that the volume of pores is the largest within this pore size range. As the pore size increases, the pore volume decreases rapidly. In the range greater than 100μm, the pore volume is almost close to zero, indicating that the pores of this material are mainly concentrated in the small pore size range. The porosity of this material is 70.7% and the total pore area is 1.4m 2 / g. These values indicate that the AN-AMPS-AAO material has a higher porosity and a larger specific surface area, which helps to improve its adsorption performance.
[0050] Figure 3 The infrared spectra of four samples are AN-AMPS-AAO, AN-AMPS, AMPS and AN. AN-AMPS-AAO has a wavelength of 3500-3000 cm -1 The region showed broad peaks, indicating the presence of -OH or -NH groups. All samples showed a peak at 1700 cm -1 There is a strong absorption peak near , which is usually related to the stretching vibration of the carbonyl group (C=O). The spectra of AN-AMPS-AAO and AN-AMPS have more hydrogen bonds or polar group characteristics in the high wavenumber region, while the peaks of AMPS and AN samples are more concentrated in the low wavenumber region, indicating that their molecular structures are relatively simple. Overall, AN-AMPS-AAO has a complex functional group structure, indicating the successful preparation of the cryogel.
[0051] Figure 4 This is a photo of the 3D-printed customized 3D-AN-AMPS-AAO cryogel adsorbent prepared in Example 1, which can be printed into a preset shape.
[0052] Embodiment 2:
[0053] (1) Preparation of macroporous flexible cryogel (AN-AMPS)
[0054] 0.75 mL AN, 0.45 g AMPS and 0.12 g MBA were added to 12 mL deionized water and stirred continuously until completely dissolved. Subsequently, the pH value of the solution was adjusted to neutral, recorded as solution A. A mixed aqueous solution of tetramethylethylenediamine (TEMED) and ammonium persulfate (APS) with a molar concentration of 0.03 M was prepared with pure water, recorded as solution B. Solution A and solution B were placed in a standard refrigerator freezer at -18°C for 2.5 minutes, and then solution A and solution B were mixed in a volume ratio of 1:1 and reacted in a refrigerator freezer at -18°C for another 6 hours. After the reaction was completed, the sample was thawed at room temperature to melt the ice crystals in the frozen gel 3D network. Subsequently, it was thoroughly washed with a mixed solution of pure water and methanol, and the resulting material was freeze-dried to obtain AN-AMPS.
[0055] (2) Preparation of amidoxime functionalized macroporous cryogel (AN-AMPS-AAO)
[0056] Add 2 g NH 2 OH·HCl, 0.75 g Na 2 CO 3 and 0.4 g NaOH. The solution was stirred at 30 °C for 3 h. Subsequently, a certain amount of dried cryogel was added to the solution and continued to react at 60 °C for 10 h, and then thoroughly washed with a mixed solution of pure water and methanol. Subsequently, the obtained cryogel was freeze-dried to obtain the product AN-AMPS-AAO.
[0057] (3) Preparation of customized cryogel (3D-AN-AMPS-AAO) using 3D printing technology
[0058] 50 mg of sodium alginate, 100 mg of AN-AMPS-AAO, and 1 mL of deionized water were uniformly mixed and shaped as needed, and then the resulting sample with a customized shape was placed in 4 wt% CaCl 2 The sample was then washed with deionized water and freeze-dried to obtain the final 3D cryogel (3D-AN-AMPS-AAO).
[0059] Embodiment 3:
[0060] (1) Preparation of macroporous flexible cryogel (AN-AMPS)
[0061] 3 mL AN, 1.8 g AMPS and 0.48 g MBA were added to 48 mL deionized water and stirred continuously until completely dissolved. Subsequently, the pH value of the solution was adjusted to neutral and recorded as solution A. A mixed aqueous solution of tetramethylethylenediamine (TEMED) and ammonium persulfate (APS) with a molar concentration of 0.12 M was prepared with pure water and recorded as solution B. Solution A and solution B were placed in a standard refrigerator freezer at -18°C and frozen for 10 minutes. Then, solution A and solution B were mixed in a volume ratio of 1:1 and reacted in a refrigerator freezer at -18°C for another 24 hours. After the reaction was completed, the sample was thawed at room temperature to melt the ice crystals in the frozen gel 3D network. Subsequently, it was thoroughly washed with a mixed solution of pure water and methanol, and the resulting material was freeze-dried to obtain AN-AMPS. (2) Preparation of amidoxime functionalized macroporous cryogel (AN-AMPS-AAO)
[0062] Add 8 g NH 2 OH·HCl, 3g Na 2 CO3 and 1.6 g NaOH. The solution was stirred at 40 °C for 3 h. Subsequently, a certain amount of dried cryogel was added to the solution and continued to react at 70 °C for 30 h, and then thoroughly washed with a mixed solution of pure water and methanol. Subsequently, the obtained cryogel was freeze-dried to obtain the product AN-AMPS-AAO.
[0063] (3) Preparation of customized cryogel (3D-AN-AMPS-AAO) using 3D printing technology
[0064] 200 mg of sodium alginate, 300 mg of AN-AMPS-AAO, and 4 mL of deionized water were uniformly mixed and shaped as needed, and then the resulting sample with a customized shape was placed in 16 wt% CaCl 2 The sample was then washed with deionized water and freeze-dried to obtain the final 3D cryogel (3D-AN-AMPS-AAO).
[0065] Embodiment 4:
[0066] Accurately weigh 4 groups of 2 mg of AN-AMPS-AAO adsorbent prepared under the conditions described in Example 1, add them to 5 mL of palladium ion solution with pH values of 1, 2, 3, and 4 and a concentration of 100 mg / L, respectively, place them on a shaker at 25°C for adsorption for 2 hours, and then collect the supernatant. The remaining palladium ion concentration in the solution was detected by inductively coupled plasma optical emission spectrometry (ICP-OES), and three groups of parallel experiments were performed under each condition. The results are shown in Figure 2. Figure 5 As shown, when the pH value is 4, the AN-AMPS-AAO adsorbent prepared in Example 1 exhibits the highest adsorption capacity.
[0067] Embodiment 5:
[0068] Accurately weigh 7 portions of 2 mg of AN-AMPS-AAO adsorbent, add them to 5 mL of a palladium ion solution with a concentration of 100 mg / L and a pH value of 4, place them on a shaker at 25°C and adsorb for 5, 10, 15, 30, 60, 120, and 360 min, and collect the supernatant. The remaining palladium ion concentration in the solution was detected by inductively coupled plasma optical emission spectrometry (ICP-OES), and three parallel experiments were performed under each condition. Figure 6 The adsorption kinetics of Pd(II) by AN-AMPS-AAO prepared in Example 1 reached adsorption equilibrium within 120 min, and the data were fitted, calculated and analyzed using the Pseudo first-order model and the Pseudo second-order model, respectively.
[0069] Embodiment 6:
[0070] Accurately weigh 6 portions of 2 mg of AN-AMPS-AAO adsorbent, add 5 mL of palladium ion solution, the solution concentrations are 50, 100, 200, 300, 400, 500 mg / L, pH is 4. Place on a shaker for adsorption at 25°C, 35°C and 45°C for 1 hour, collect the supernatant, and detect the remaining palladium ion concentration in the solution by inductively coupled plasma optical emission spectrometry (ICP-OES), and perform three parallel experiments. Figure 7 The adsorption isotherm of Pd(II) by AN-AMPS-AAO prepared in Example 1 is shown, and the adsorption data are fitted using the Langmuir and Freundlich models. The results show that within the test temperature range, the adsorption capacity increases with increasing temperature.
[0071] Embodiment 7:
[0072] 2 mg of AN-AMPS-AAO adsorbent was accurately weighed and added to 5 mL of simulated electronic waste leaching mixed solution with a concentration of 50 mg / L of Ca(Ⅱ), Cu(Ⅱ), Fe(Ⅲ), K(Ⅰ), Mg(Ⅱ), Ni(Ⅱ), Zn(Ⅱ), and Pd(Ⅱ), respectively, and placed on a shaker for adsorption for 1 hour at 25°C. After collecting the supernatant, the residual concentration of various ions in the solution was detected by inductively coupled plasma optical emission spectrometry (ICP-OES), and three sets of parallel experiments were performed. Figure 8 It shows that in the presence of numerous interfering ions, the AN-AMPS-AAO adsorbent prepared in Example 1 still exhibits the highest adsorption capacity for Pd(II), which is much higher than the adsorption capacity of other metal ions.
[0073] Embodiment 8:
[0074] Accurately weigh 2 mg of AN-AMPS-AAO adsorbent, add 5 mL of a palladium ion solution with a pH value of 4 and a concentration of 100 mg / L, place it on a shaker at 25°C for adsorption for 2 hours, take the supernatant, wash the remaining frozen gel with deionized water, add 5 mL of an eluent mixed with 0.5 mol / L thiourea and 0.1 mol / L hydrochloric acid, place it on a shaker for desorption for 1 hour, take out the adsorbent, wash it with deionized water and dry it. This is one cycle, and a total of five cycles are performed. The palladium ion concentration in the solution is detected by inductively coupled plasma optical emission spectrometry (ICP-OES), and three parallel experiments are performed. Fig. 9 As shown, the adsorption capacity of AN-AMPS-AAO prepared in Example 1 for Pd(II) did not decrease significantly after 5 adsorption-desorption cycles, proving that it has good regeneration and recycling capabilities.
[0075] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a 3D printable macroporous cryogel monolithic adsorbent, characterized by the following steps: (1) Preparation of macroporous flexible cryogel AN-AMPS: A certain amount of acrylonitrile AN, 2-acrylamido-2-methylpropanesulfonic acid AMPS and methylenebisacrylamide MBA were added into a certain amount of deionized water and stirred continuously until they were completely dissolved; then, the pH value of the solution was adjusted to neutral, which was recorded as solution A; Use pure water to prepare a mixed aqueous solution of tetramethylethylenediamine TEMED and ammonium persulfate APS with a molar concentration of c1, which is recorded as solution B; Solution A and solution B are placed in a standard refrigerator freezer for a certain period of time t1, and then solution A and solution B are mixed in proportion and reacted in the refrigerator freezer for a certain period of time t2; after the reaction is completed, the sample is thawed at room temperature to melt the ice crystals in the frozen gel 3D network, and then thoroughly washed with a mixed solution of pure water and methanol, and the obtained material is freeze-dried to obtain gel AN-AMPS; (2) Preparation of amidoxime-functionalized macroporous cryogel AN-AMPS-AAO: Add hydroxylamine hydrochloride NH2OH·HCl, sodium carbonate Na2CO3 and sodium hydroxide NaOH to dimethylformamide DMF, and stir the mixed solution at a certain temperature T1; then, add the gel AN-AMPS obtained in step (1) to the mixed solution, and continue to react at a certain temperature T2 for a certain time t3, and then thoroughly wash with a mixed solution of pure water and methanol, and then freeze-dry the obtained frozen gel to obtain the product AN-AMPS-AAO; (3) Preparation of customized cryogel 3D-AN-AMPS-AAO using 3D printing technology: Sodium alginate, AN-AMPS-AAO and deionized water in a certain mass ratio are uniformly mixed and shaped as needed, and then the resulting sample with a customized shape is placed in a certain weight percentage of CaCl2 aqueous solution and allowed to stand for a period of time to ensure thorough cross-linking and curing; then, the sample is washed with deionized water and freeze-dried to obtain the final 3D cryogel, namely 3D-AN-AMPS-AAO.
2. The method for preparing a 3D printable macroporous cryogel monolithic adsorbent according to claim 1, characterized in that: In the solution A of step (1), the dosage ratio of AN, AMPS, MBA and water is 0.75-3 mL: 0.45-1.8 g: 0.12-0.48 g: 12-48 mL; In the solution B of step (1), the molar concentrations c1 of TEMED and APS are both 0.03-0.12 M; The volume ratio of solution A to solution B is 1:
1.
3. The method for preparing a 3D printable macroporous cryogel monolithic adsorbent according to claim 1, characterized in that: In step (1), the freezing temperature is -18°C, the freezing time t1 is 2.5-10 min, and the reaction time t2 is 6-24 h.
4. The method for preparing a 3D printable macroporous cryogel monolithic adsorbent according to claim 1, characterized in that: In step (2), the usage ratio of DMF, NH2OH·HCl, Na2CO3 and NaOH is 50-200mL: 2-8g: 0.75-3g: 0.4-1.6g.
5. The method for preparing a 3D printable macroporous cryogel monolithic adsorbent according to claim 1, characterized in that: In step (2), during the stirring, the temperature T1 is 30-40° C. and the stirring time is 3 h.
6. The method for preparing a 3D printable macroporous cryogel monolithic adsorbent according to claim 1, characterized in that: In step (2), the reaction temperature T2 is 60-70°C, and the reaction time t3 is 10-30h.
7. The method for preparing a 3D printable macroporous cryogel monolithic adsorbent according to claim 1, characterized in that: In step (3), the dosage ratio of the sodium alginate, AN-AMPS-AAO and deionized water is 50-200 mg: 100-300 mg: 1-4 mL.
8. The method for preparing a 3D printable macroporous cryogel monolithic adsorbent according to claim 1, characterized in that: In step (3), the weight percentage of the CaCl2 aqueous solution is 4-16wt%.
9. The method for preparing a 3D printable macroporous cryogel monolithic adsorbent according to claim 1, characterized in that: In step (3), the cross-linking and curing time is 6-24 hours.
10. Use of the cryogel 3D-AN-AMPS-AAO prepared by the preparation method according to any one of claims 1 to 9 for selective separation of palladium.
